SK4 channels modulate Ca2+ signalling and cell cycle progression in murine breast cancer. Issue 9 (26th June 2017) - Steudel, Friederike A.; Mohr, Corinna J.; Stegen, Benjamin; Nguyen, Hoang Y.; Barnert, Andrea; Steinle, Marc; Beer‐Hammer, Sandra; Koch, Pierre; Lo, Wing‐Yee; Schroth, Werner; Hoppe, Reiner; Brauch, Hiltrud; et al.
Abstract : Oncogenic signalling via Ca 2+ ‐activated K + channels of intermediate conductance (SK4, also known as KCa 3.1 or IK) has been implicated in different cancer entities including breast cancer. Yet, the role of endogenous SK4 channels for tumorigenesis is unclear. Herein, we generated SK4‐negative tumours by crossing SK4‐deficient (SK4 KO) mice to the polyoma middle T‐antigen (PyMT) and epidermal growth factor receptor 2 (cNeu) breast cancer models in which oncogene expression is driven by the retroviral promoter MMTV. Survival parameters and tumour progression were studied in cancer‐prone SK4 KO in comparison with wild‐type (WT) mice and in a syngeneic orthotopic mouse model following transplantation of SK4‐negative or WT tumour cells. SK4 activity was modulated by genetic or pharmacological means using the SK4 inhibitor TRAM‐34 in order to establish the role of breast tumour SK4 for cell growth, electrophysiological signalling, and [Ca 2+ ]i oscillations. Ablation of SK4 and TRAM‐34 treatment reduced the SK4‐generated current fraction, growth factor‐dependent Ca 2+ entry, cell cycle progression and the proliferation rate of MMTV‐PyMT tumour cells. In vivo, PyMT oncogene‐driven tumorigenesis was only marginally affected by the global lack of SK4, whereas tumour progression was significantly delayed after orthotopic implantation of MMTV‐PyMT SK4 KO breast tumour cells. However, overall survival and progression‐free survival time in the MMTV‐cNeu mouse model were significantly extended in the absence of SK4. Collectively, our data from murine breast cancer models indicate that SK4 activity is crucial for cell cycle control. Thus, the modulation of this channel should be further investigated towards a potential improvement of existing antitumour strategies in human breast cancer. Abstract : The oncogenic potential of the Ca 2+ ‐activated K + channel of intermediate conductance (SK4) was previously defined by the in vitro response of tumour cells to pharmacological SK4 modulators. Hence, we assessed SK4‐negative breast cancer‐prone mice and a syngeneic orthotopic transplant model in order to elucidate the tumorigenic activity of endogenous SK4 channels. Our data support strong anticancer effects for tumour cell SK4 inhibition; however, the global dysfunction of SK4 in mice may also favour a tumour progression‐promoting microenvironment.